Pengaruh Harga dan Promosi terhadap Keputusan Pembelian Sepeda Motor pada PT. Rotella Persada Mandiri - Shinta Devy; Nora Anisa Br. Sinulingga (Junal Ilmu Manajemen, 2018)
This research was conducted at PT. Rotella Persada Mandiri, with the aim of research to analyze the effected of partial and simultaneous prices and promotions toward consumer purchasing decisions for motorcycles. This type of research used associative, the population were consumers who came to visit and buy two-wheeled vehicle products in March 2019 amount of 500 consumers, taking samples using the Slovin formula as many as 83 respondents. Research data sources used primary data and secondary data, data collection techniques using library studies, questionnaires and observations. The data analysis technique used multiple linear regression, classic assumption test and hypothesis test. Based on the results of the study indicated that partially the price has significant effectedtoward the motorcycle of purchase decisions, while the promotion did not have significant effectedtoward purchasing decisions. Simultaneously, prices and promotions have significant effected toward consumer purchasing decisions at PT. Rotella Persada Mandiri. The R square (R2) coefficient of 0.888 indicated that consumer purchasing decisions could be explained by price and promotion amount of88.8% and the others 11.2% could be explained by other variables did not examined.